Evaluation of the Antibacterial Activity of Natural Honey Against Common Pathogenic Bacteria - Ibrahim Mohamed altelawi (Journal of Libyan Academy Bani Walid, 2025)
"This study aimed to evaluate the antibacterial activity of natural honey against selected common species of pathogenic bacteria, including both Gram-positive and Gram-negative strains. Eighteen bacterial isolates were obtained from clinical samples collected from Al-Qarawy Ben Nasser Hospital and identified using biochemical tests and the VITEK system. The antibacterial potential of natural honey was assessed using the agar well diffusion method at four different concentrations (25%, 50%, 75%, and 100%)". Results demonstrated that honey exhibited a broad-spectrum antibacterial effect against "Staphylococcus aureus, Streptococcus pneumoniae, Escherichia coli, Klebsiella pneumoniae, and Pseudomonas aeruginosa. The inhibition zones ranged between 3–25 mm, with the strongest inhibition observed at the 100% concentration. Statistical comparison indicated no significant difference between Gram-positive and Gram-negative bacteria in their susceptibility to honey". The study concludes that natural honey possesses significant antibacterial properties that may serve as an alternative or complementary agent to conventional antibiotics, especially in combating antibiotic-resistant bacteria.